The Relationship between Diabetes Mellitus and Periodontal Disease (Journal of Pharmaceutical Negative Results, 2023)
Objective: The aims to elucidate the major complications of diabetes, the increased risk and severity of periodontitis and to provide a basic mechanism for the association of diabetes mellitus with periodontal disease.Materials and Methods: An initial search was conducted of the PubMed, Elsevier and Science Direct databases Online to evaluate articles on the relationship of diabetes mellitus to periodontal disease. The initial result of this search was 4037 articles. Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) by using the system Population/Problem, Intervention, Comparison/Control, and Outcome (PICO). After manual selection, only 5 articles will be synthesized.Results: From these five articles it was found that Diabetes mellitus can increase the risk of severity and prevalence of periodontal disease caused by an increase in inflammatory cells in the periodontal tissue.Conclusion: Diabetes can increase the risk of the severity and prevalence of periodontal disease.